A New Extractive Spectrophotometric Method for the Estimation of Alosetron - Y. Kranthi Kumar, K.Vanitha Prakash , Guthi Lavanya, Ravi Pratap Pulla (Journal of Applied Pharmaceutical Science, 2014)
Two simple, accurate, rapid and sensitive Methods (A and B) have been developed for the estimation of Alosetron in its pharmaceutical dosage form. The Method A is based on the formation yellow colored chromogen, due to reaction of Alosetron Hydrochloride with Metanil yellow dye, formation of ion association complexes of the drug with dyes in phosphate buffer of pH 3.6 followed by their extraction in chloroform which exhibits λmax at 410 nm. The Method B is based on the formation of light yellow colored chromogen due to reaction of Alosetron Hydrochloride with Methyl Orange dye, formation of ion association complexes of the drug with dyes in phosphate buffer of pH 3.6 followed by their extraction in chloroform, which exhibits λ max at 422 nm. The absorbance-concentration plot is linear over the range of 5-60 mcg/mL for Method A and 50-120 mcg/mL for Method B. Results of analysis for all the methods were validated statistically and by recovery studies. The proposed methods are precise, accurate, economical and sensitive for the estimation of Alosetron in bulk drug and in its Tablet dosage form.
Keywords: Alosetron, Metanil Yellow, Methyl Orange.